Pre-breeding for small grain cereals: How to meet future challenges of food supply under a changing climate - Bioversity International; European Cooperative Programme for Plant Genetic Resources (2010)
Concept note “Pre-breeding for small grain cereals”, ECPGR Cereals Network and ECPGR Working Group on Barley.